UMP Student Team Competes at NMEPC 2022 - Halizan, Mohmood (2023)
MELAKA, May 14, 2023 - A team from Universiti Malaysia Pahang (UMP) that introduced the Hand Obstacle Detector (HOD) prototype idea, focusing on developing assistive technology for the use of persons with disabilities (PWDs) during walking, won a consolation prize in the Technology and Innovation category at the National Micro Enterprise Pitching Competition (NMEPC) organized by the Ministry of Higher Education (KPT) in collaboration with the managing institution, Universiti Teknikal Malaysia Melaka (UTeM).